Response of Posidonia oceanica (L.) Delile and Its Associated N2 Fixers to Different Combinations of Temperature and Light Levels - García-Márquez, Manuela Gertrudis; Fernández-Juárez, Víctor; Rodríguez-Castañeda, José Carlos; Agawin, Nona S. R. (Frontiers in Marine Science, 2022)
The increasing occurrence of heat waves and water turbidity are threats for the persistence of seagrass meadows and their effects on the productivity of seagrasses and the functioning of their associated microorganisms have not been studied extensively. The purpose of this study was to assess the effects of different light levels and temperatures on Posidonia oceanica, the endemic seagrass species in the Mediterranean Sea, and their N2 fixing community, which contributes importantly to the nitrogen requirements and high productivity of the plants. Aquarium experiments were conducted in winter when the plants are more vulnerable to changes in temperature, subjecting them to short-term exposures to ambient (15.5 ºC) and elevated temperatures (ambient+5.5 ºC) and at limited (13 µmol photons m-2 s-1) and saturating light conditions (124 µmol photons m-2 s-1). Primary production, chlorophyll content, reactive oxygen species production, polyphenols content, the nifH gene expression, N2 fixation and alkaline phosphatase activities were measured in different plant tissues. Plants incubated at ambient temperature and high light exhibited enhanced total chlorophyll production. Significantly higher gross and net primary production rates were also recorded under ambient temperature and high light conditions, which were approximately two-fold compared to the rest of the treatments. The oxidative stress analyses revealed increased production of reactive oxygen species in young leaves incubated at ambient temperature and saturating light, while the polyphenols content in top leaves was considerably higher under elevated temperatures. In contrast, N2 fixation and alkaline phosphatase rates were significantly higher under elevated temperature and low light levels. The presence of the N2 fixing phylotypes UCYN-A, -B and -C was detected through genetic analyses, with UCYN-B demonstrating the highest nifH gene transcription levels at elevated temperatures. These findings emphasize the significant role of irradiance on the productivity of P. oceanica and the temperature dependence of the N2 fixation process in winter.